The Effects of Intermittent Trunk Flexion With and Without Support on Sitting Balance in Young Adults - Voglar, Matej; Kozinc, Žiga; Kingma, Idsart; van Dieën, Jaap H.; Šarabon, Nejc (Frontiers in Human Neuroscience, 2022)
Prolonged trunk flexion is known to affect passive and active stabilization of the trunk. Previous studies have evaluated changes in spinal range of motion, muscle activity and reflex behavior induced by prolonged trunk flexion, whereas the effect on sitting postural control is vastly underexplored. In this study, we compared the effects of supported and unsupported trunk intermittent flexion on center of pressure (CoP) motion during sitting on an unstable seat. Participants (n = 21; 11 males, 23.2 ± 2.0 years; 10 females, age 24.3 ± 4.0) were exposed to 1-hour intermittent (60-s sets with 30 s of rest) trunk flexion (80 % of the maximal range of motion) and CoP root mean square distance, velocity and frequency before and after the exposure were assessed. Contrary to our hypothesis, there were no main effects of exposure (pre. vs. post flexion protocol; p = 0.128-0.709), no main effects of condition (supported vs. unsupported; p = 0.134-0.931), and no interaction between exposure and condition (p = 0.163-0.912). Our results indicate that prolonged intermittent flexion does not induce any changes in CoP motion during a seated balance task, regardless of the presence of a trunk support during prolonged intermittent flexion. This suggests a successful compensation of decreased passive stiffness by increased reflex activity.